Efforts to Combat Drug Abuse Crimes Committed by Children at The West Kalimantan Regional Police - Zahedi, Irwan; Tri Bawono, Bambang (Jurnal Hukum Khaira Ummah, 2025)
Legally, narcotics are only used for scientific development and health services, but in reality, they are often abused. Drug use has become a business venture and has had a detrimental impact on the mental, physical, and psychological well-being of the younger generation. Law Number 35 of 2009 concerning Narcotics has regulated the types of very severe criminal sanctions against perpetrators of narcotics crimes. The method is a basic process regarding the procedure for finding a solution to a problem, while research is a careful examination of signs in order to obtain human knowledge, so the research method can be interpreted as the basic procedure for finding a solution to existing problems in carrying out research related to efforts to overcome the crime of narcotics abuse committed by children at the West Kalimantan Regional Police. To realize a just and effective drug handling system, a shift in the social paradigm and a more humanistic legal culture is needed, strengthening legal certainty through consistent and transparent enforcement, and increasing rehabilitation capacity and coordination between institutions. Thus, the law becomes not only a repressive tool, but also an instrument of recovery that provides tangible benefits for child victims of drug abuse and society at large.